New analog filter design possibilities with MOSFET-C technique - Başaran, Emir Yasin. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2021., 2021)
There are many analog lter examples available in the literature to address various needs, such as certain bandwidth, transfer function, and low power consumption. To meet such requirements, operational ampli er based analog lters are widely used in the last several decades and they are still popular. However, today's applications expect analog design engineers to achieve low power consumption and small chip areas. Therefore, much research has been done on MOS based circuits because of their easy IC implementable features. There are some designs, called as MOS-only, primarily relying on utilizing transconductance gm and gate-to-source capacitance (Cgs) of the MOSFET instead of external passive components. Even though MOS-only design approach has some attractive features, width and length of transistors must be set in accordance with strict rules. We have included some on-chip capacitors, such that the e ect of non-ideal MOS factors on lter parameters are moderated to some extent. In this thesis, we have designed novel current mode agile, transimpedance, transconductance, and voltage mode analog lters. Besides that, to demonstrate circuit operation we have chosen some of them and biased properly. Since we have provided transfer functions by taking non-ideal MOS parameters into account, we are able to predict circuit behaviour under electronic adjustments. By relying on this, we have tuned our designs under di erent bias possibilities without violating saturation conditions. Such methodology, of course, broadens the application range of designs. Additionally, how the biased designs behave under various environmental conditions is examined by introducing temperature e ects and possible implementation errors.
Keywords: Electric filters -- Design and construction.; Metal oxide semiconductor field-effect transistors.